T2 Subphenotypes in patients with severe acute respiratory failure requiring extracorporeal membrane oxygenation. (11th November 2022) - Reddy, K; Millar, JE; Malfertheiner, MV; Sinha, P; Antcliffe, D; Calfee, CS; O'Kane, CM; Müller, T; McAuley, DF
Abstract : Introduction and Objectives: Hyperinflammatory and hypoinflammatory subphenotypes have been identified in patients with the acute respiratory distress syndrome (ARDS) which consistently have different clinical characteristics, biomarker profiles and outcomes. These subphenotypes may not be specific to ARDS. Patients on veno-venous extracorporeal membrane oxygenation (VV ECMO) represent a distinct population in which subphenotypes have not been previously identified. The aim of this research was to identify if subphenotypes are present in a mixed cohort of patients with severe acute respiratory failure requiring VV ECMO. Methods: Adult patients requiring VV ECMO from a single centre in Regensburg, Germany were included. Clinical and ventilation data were recorded immediately prior to initiation of ECMO and on the first day thereafter. The inflammatory cytokines interleukin-6 (IL-6), interleukin-8 (IL-8), and tumour necrosis factor alpha (TNF-a) were measured by ELISA from plasma samples taken immediately prior to initiation of ECMO. Latent class analysis (LCA) was used to identify subphenotypes and included both clinical and biomarker variables. Subphenotype association with hospital mortality was assessed. Results: 437 patients initiated on VV ECMO were included. The most common indications for ECMO were viral infection (15%), bacterial infection (41%), and post-operative (16%). Using LCA, a two-class model was a better fit for the cohort than a one-class model (p < 0.001). There were 322 (74%) patients in Class 1 and 115 patients in Class 2 (26%). Class 2 was characterised higher cytokine concentrations, more metabolic acidosis, and more non-pulmonary organ failure, consistent with the ARDS hyperinflammatory subphenotype. Patients with the hyperinflammatory subphenotype (Class 2) had worse hospital mortality (49% vs. 31%, p = 0.001) than those with the hypoinflammatory subphenotype (Class 1). Discriminant variables in the LCA model are detailed in figure 1 . Conclusions: Two subphenotypes were identified in patients with severe acute respiratory failure requiring ECMO, with characteristics similar to those previously identified in data from non-ECMO ARDS patients, including worse outcomes in the hyperinflammatory subphenotype. These subphenotypes could be targeted with precision medicine treatments in future trials of patients on VV ECMO.